Genesis analysis and effective development of normal pressure shale gas reservoir: A case of Wufeng-Longmaxi shale gas reservoir in southeast margin of Sichuan Basin - XUE Gang, XIONG Wei, ZHANG Peixian (Youqicang pingjia yu kaifa)
There are two types of shale gas reservoirs in the Wufeng-Longmaxi shale formation of southeast margin of Sichuan Basin: normal pressure shale gas reservoir in Wulong residual syncline and abnormal over-pressure shale gas reservoir in Fuling anticline. This study takes an integrated geology-engineering approach to analyze the genesis and formation mechanisms of normal pressure shale gas reservoirs in the Wulong area. The analysis is based on shale burial history curves, drilling data, horizontal well fracturing parameters, and the geological characteristics specific to normal pressure shale gas reservoirs. Combined with the actual production effects of two horizontal shale gas wells, the fracturing process parameters of normal pressure shale gas reservoirs are optimised. Then three main points have been obtained in this study: ①The normal pressure shale gas reservoir of the Wufeng-Longmaxi Formation in Wulong area is formed during the structural destruction adjustment of the Yanshanian and Himalayan tectonic periods. ②The shale gas escaping caused by tectonic elevation is the main reason for the formation of normal pressure shale gas. ③Compared with the Marcellus normal pressure shale gas reservoir, Wulong normal pressure shale gas reservoir has the similar geological characteristics, but the development effect varies greatly. The fracturing scale simulation shows that it is necessary to further optimise the horizontal well segmented fracturing parameters, increase the output of single wells, and reduce development costs. Only in this way can effective development be realised.